A-102 Antibody binding to HIV-1 infected cells as mechanism for treatment of HIV infection. (April 2018) - Ferrari, Guido; Nordstrom, Jeffrey; Koenig, Scott; Sung, Julia; Margolis, David; Haynes, Barton
Abstract : Anti-HIV antibody function is not limited to capturing free virus but also includes the recognition of HIV-1 infected cells. Both neutralizing and nonneutralizing antibody responses recognizing HIV-1 envelope epitopes expressed on the cellular membrane can recruit Fc receptor-bearing cells and direct their cytotoxic activity against the infected cells. We can leverage on our ability to use monoclonal antibody and monoclonal antibody-based molecules to protect from and treat HIV-1 infection.